Assessing the species composition of tropical eels (Anguillidae) in Aceh Waters, Indonesia, with DNA barcoding gene cox1. [version 1; referees: 1 approved, 2 approved with reservations] - Muchlisin, Zainal A.; Batubara, Agung Setia; Fadli, Nur; Muhammadar, Abdullah A.; Utami, Afrita Ida; Nurul Farhana, Nurul Farhana; Mohd Nor, Siti Azizah (F1000Research, 2017)
The objective of the present study was to evaluate the species diversity of eels native to Aceh waters based on genetic data. Sampling was conducted in western coast waters of Aceh Province, Indonesia, from July to August 2016. Genomic DNA was extracted from the samples, a genomic region from the 5’ region of the cox1 gene was amplified and sequenced, and this was then used to analyse genetic variation. The genetic sequences were blasted into the NCBI database. Based on this analysis there were three valid species of eels that occurred in Aceh waters, namely Anguilla marmorata, A. bicolor bicolor, and A. bengalensis bengalensis.